Sistem Informasi Panti Asuhan Hindu Dharma Jati I Berbasis Web Menggunakan Framework Laravel 12 - I Kadek Agus Kartadhi Mahardika; Kadek Oky Sanjaya; I Putu Mahendra Adi Wardana (RESI : Jurnal Riset Sistem Informasi, 2026)
The use of information technology in the social sector continues to develop in order to improve service efficiency and transparency. Hindu Dharma Jati I Orphanage faces challenges in delivering information and managing donations due to the absence of a self-managed digital platform. This study aims to design and develop a web-based information system to support information dissemination and online donation processes in a more structured manner. The system was developed using the ADDIE method and the Laravel 12 framework, and tested using blackbox testing and user acceptance testing (UAT). The test was conducted involving a sample of 15 users and 5 admins. The results show that the system is able to provide structured information and facilitate online donations for both the community and orphanage administrators. Based on the UAT results, the system showed a very good level of acceptance with an average value exceeding 90% on the user page and 97%–100% on the admin page, so it was declared acceptable and able to support user needs effectively and efficiently.